Polarity Sensitivity as (Non)Veridical Dependency. - Giannakidou, Anastasia (John Benjamins Pub. Co., 1998)
Polarity phenomena have been known to linguists since Klima's seminal work on English negation. In this monograph Giannakidou presents a novel theory of polarity which avoids the empirical and conceptual problems of previous approaches by introducing a notion wider than negation and downward entailment: (non)veridicality. The leading idea is that the various polarity phenomena observed in language are manifestations of the dependency of certain expessions, i.e. polarity items, to the (non)veridicality of the context of appearence. Dependencies to negation or downward entailment emerge as subca.